Patient-Reported Outcomes in Clinical Trials: Lessons from the Blood and Marrow Transplant Clinical Trials Network - Betty K. Hamilton; Catherine J Lee; Deborah Mattila; Areej El-Jawahri; Rachel N. Cusatis; Ruta Brazauskas; Anthony D. Sung; Rachel Phelan; Mary M Horowitz; Stephanie J. Lee (Blood Advances, 2026)
The Blood and Marrow Transplant Clinical Trials Network performs multi-center Phase 2 and Phase 3 clinical trials and has incorporated patient reported outcome (PRO) measures into study protocols since its inception. As with clinical data, collection and analysis of this type of information requires rigor to allow valid conclusions. This paper summarizes our experience with PROs over the last 25 years and reports on the quality of PRO reporting as well as lessons learned in this academic network setting.